Designing Emotion Methods and Strategies for Designers - Roth, Mareike; Saiz, Oliver (Birkhäuser, 2022)
How does design make the indestructible character of a drill tangible? Why does a brand become a trusted friend? And what emotions should intelligent gardening tools actually radiate? The accurate communication and design of emotional worlds remain one of the greatest challenges for companies and professional design. Designing Emotion offers practical support here. Based on current research from neuroscience and psychology, the book presents tools for systematically analysing emotions and controlling them through precise use of form, colour and material. In addition to case studies and interviews, this edition offers insights into the design practice of successful companies. Provides professional design instruments for influencing emotions Includes a folding poster for the use of "emotion grid" With illustrative product analyses